2008
DOI: 10.1093/cvr/cvn045
|View full text |Cite
|
Sign up to set email alerts
|

Besides adhesion: new perspectives of integrin functions in angiogenesis

Abstract: During angiogenic remodelling in embryo and adult life, endothelial cells lining blood vessel walls dynamically modify their integrin-mediated adhesive contacts with the surrounding extracellular matrix. However, besides regulating cell adhesion and migration, integrins dynamically participate in a network with soluble molecules and their receptors. Angiogenesis is characterized by opposing autocrine and paracrine loops of growth factors and semaphorins that regulate the activation of integrins on the endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 113 publications
1
42
0
Order By: Relevance
“…One observation was that tumors formed by SEMA3F-expressing cells display reduced vascularization. Consistent with the inhibition of integrin activation by plexin signaling (review: Serini et al, 2008), reduced b3 integrin activation was found in SEMA3F-transfected H157 lung cancer cells, along with reduced adhesion to fibronectin and vitronectin (Potiron et al, 2007. Additional signaling changes induced by SEMA3F in lung cancer cells included loss of activated ERK1/2, AKT and STAT3, with downstream inhibition of HIF1a translation and VEGF 165 mRNA expression.…”
Section: Diseasesupporting
confidence: 68%
See 1 more Smart Citation
“…One observation was that tumors formed by SEMA3F-expressing cells display reduced vascularization. Consistent with the inhibition of integrin activation by plexin signaling (review: Serini et al, 2008), reduced b3 integrin activation was found in SEMA3F-transfected H157 lung cancer cells, along with reduced adhesion to fibronectin and vitronectin (Potiron et al, 2007. Additional signaling changes induced by SEMA3F in lung cancer cells included loss of activated ERK1/2, AKT and STAT3, with downstream inhibition of HIF1a translation and VEGF 165 mRNA expression.…”
Section: Diseasesupporting
confidence: 68%
“…As a consequence, R-Ras is inactivated by the GAP activity of plexins (step "5"), leading to integrin inhibition. Also, free FARP2 competes with talin for binding to PIPKIγ661 (step "6"), impairing talin binding to beta-integrin, which is necessary for focal adhesion (for reviews see Yazdani and Terman, 2006;Serini et al, 2008). Activation of type-A plexins by SEMA3s induces phosphorylation of CRMP2 (Collapsin Response Mediator Protein) which hinders its tubulin binding activity.…”
Section: Functionmentioning
confidence: 99%
“…The common targets of semaphorins are the actin cytoskeleton and focal adhesions; the latter are dynamic cell-to-extracellular matrix adhesive structures that are assembled upon integrin engagement. Semaphorin signaling affects focal adhesion assembly/disassembly and induces cytoskeletal remodeling, thus consequently affecting cell shape, attachment to the extracellular matrix, cell motility, and cell migration [12,13].…”
Section: Semaphorinsmentioning
confidence: 99%
“…Integrins are heterodimeric cell surface molecules involved in cell matrix adhesion as well as outside-in and inside-out signaling (24). The integrins α v β 3 , α v β 5 , and α 5 β 1 have been characterized as prototypic molecules of angiogenic ECs.…”
Section: Introductionmentioning
confidence: 99%